Driving Sustainability of Minibus Taxi Industry in South Africa - Mathu, Kenneth (European Journal of Applied Sciences, 2022)
Background: The minibus taxi is the leading commuter transport mode in South Africa, with a market share of about 70%. Despite the industry’s positive socio-economic contributions to the country, the management is handicapped by the industry’s informal nature among other issues. This study explored the sustainability initiatives for minibus taxi industry in South Africa, as the country and the rest of the world pursued the net zero emissions target by 2050. Method: The study was grounded in the theories of sustainable development and change management, pursued qualitative research methodology and constructivism research paradigm. Non-probability sampling process was used in selecting the participants from the minibus taxi industry in North West province, South Africa. The participants were interviewed and the interviews recorded, transcribed, coded and analysed for results through content analysis. Results: The outcome overwhelmingly preferred formalisation of the industry, which would improve management, commuter safety and reduction of carbon emissions, which would enhance competitiveness and sustainability. Conclusion: The formalisation of the minibus taxi industry would streamline its management and facilitate faster taxi electrification, when adoption of electrical vehicles commences in the country, drastically reducing carbon emissions.